An Assessment of the Effects of Root and Tuber Expansion Project (RTEP) on the Livelihood of Cassava Processors in Kwara State, Nigeria - Achem, Bello Alli; Akangbe, Jones Adebola; Animashaun, Jubril Olayinka (International Journal of Agricultural Management and Development, 2013)
The study was carried out to assess the effects of the Root and Tuber Expansion Programme (RTEP) on the livelihood of project beneficiaries in Kwara State, Nigeria. A 3-stage sampling technique was adopted for the study, selecting a total of 80 cassava processors from two Agricultural Development Programme (ADP) zones in the State. Structured interview schedule was used as instrument to elicit primary data from processors. Descriptive statistics was used to describe the socio economic characteristics of the respondents. The t-test was used to test the hypotheses on the relationship between the income and livelihood of RTEP beneficiaries and non beneficiaries, while those on the socio economic characteristics was tested using the Mann-Whitney (U) test. The findings of the study showed that RTEP provided more than 73 percent of total cassava processing equipment in the study area. The study further revealed that there was no significant difference in the socio-economic characteristics and livelihood of RTEP and Non RTEP participants. There was however a significant difference in their income. Amongst others, the study recommended massive investment in subsidizing critical cassava processing equipment, and provision of micro-credit at low interest rates to cassava processors.